LIMITING PRESIDENTIAL TERM OF OFFICE IN INDONESIA: A DEMOCRATIC PERSPECTIVE - Hendra, Hendra -; Darmawan, Wawan Budi; Manan, Firman; Husin, Luthfi Hamzah (JWP (Jurnal Wacana Politik), 2020)
Following the amendment of the 1945 Constitution, Indonesia became one of the countries that adopted presidential government system in which the president is directly elected by the people. The interesting thing that is still hitherto controversial is the limitation of presidential term of office for no more than two periods. Our review of various literatures illustrates that there is no standard exemplar to limit or not to limit the period that must be applied in a country that adheres to presidentialism. Furthermore, if it is associated with democracy, the limitation of presidential period will cause contradiction especially with president’s accountability in which the president is directly elected by the people. Based on this, we conducted a study using qualitative method with historiography approach that aims at knowing how the periodisation of presidential term of office in Indonesia viewed from a democratic perspective. This article argues that the model of presidential period limitation for at maximum two periods must be carried out by adding the length of service to more than five years and requiring an interlude between the first and the second period. The modelling can anticipate the tendency of power abuse by incumbent while maintaining people’s support for the legitimacy of the president.